2014
DOI: 10.2478/acph-2014-0026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant Activity of Coreopsis Tinctoria Nuff. and Optimisation of Isolation by Response Surface Methodology

Abstract: Evaluation of the antioxidant activity of Coreopsis tinctoria Nuff. and optimisation of isolation by response surface methodologyThe aim of the present study was to determine the antioxidant activity of Coreopsis tinctoria flowering tops (CTFT). Studies were conducted to obtain suitable extraction conditions for chlorogenic acid, quercetin, luteolin, apigenin and kaempferol, which were identified and quantified by HPLC. Response surface methodology was employed to optimise the ultrasound-assisted extraction co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The interpretations are summarized in Table 1 and showed that both EEC and WEC were rich in flavonoid compounds, and EEC contained more constituents. These data are in agreement with the previous reports [ 13 , 18 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The interpretations are summarized in Table 1 and showed that both EEC and WEC were rich in flavonoid compounds, and EEC contained more constituents. These data are in agreement with the previous reports [ 13 , 18 ].…”
Section: Resultssupporting
confidence: 94%
“…Previous studies have shown that CTF is rich in flavonoids and polyphenols [ 13 , 18 ]. Similarly, we found that EEC and WEC contain 27.28% and 36.2% total flavonoids, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Flower infusion tea is used as a beverage to treat hypertension and hyperlipidemia [2]. Pharmacological studies have indicated that C. tinctoria exhibits some biological effects including antioxidant [3], antidiabetic [4], antihypertensive [5], and cytoprotective [1] activities. Although C. tinctoria is used for liver diseases, studies have yet to report on its hepatoprotective effect.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in Portugal, two cups per day of an infusion of CT flowering tops has been traditionally used to control diabetes (15). Pharmacological studies have shown that CT exhibits many beneficial biological activities, including antihyperlipidemic (16), antioxidative (17), antidiabetic (18), and antihypertensive (19) effects. The effects of CT are mainly attributed to its flavonoid-like polyphenols (20); however, the effects of drinking CT tea on insulin sensitivity and hepatic glucose metabolism are still unknown.…”
mentioning
confidence: 99%